Enterprise Social Media Usage and Team Performance with The Moderation of Workplace Integration: An Empirical Study of Telecommunication Sector in Pakistan - GholamReza Zandi; Muhammad Sadiq Shahid; Shakeel Ahmed; Imran Ahmed Shahzad (Journal of Information Technology Management, 2021)
Enterprise Social Media (ESM) has been normally embraced by companies to boost team performance and agility for workers. The goal of this study is to investigate the mediating effect of workplace isolation on the relationships among usage ESM, employee agility and Team Performance along with exploration of the moderating influence of workplace Integrational study model. This research adds to corporate awareness in illustrating the impact of ESM use on team performance and employee agility based on theory of social exchange, theory of information processing and the theory of transactive memory. Cross-sectional survey was employed to collect data from telecommunication firms (public & private). 400 respondents were selected through purposive sampling technique and given close ended questionnaires, 348 questionnaires were selected for further analysis; through a number of statistical tools, after screening out the filled responses. It resulted in Suggesting ESM has a favorable effect on Employee Agility and Team Performance, but the negative relationships were observed among workplace isolation and employee agility and team performance. Further, Workplace Isolation mediated the relationship among ESM, Employee Agility and Team performance. Additionally, Workplace Integration strongly moderated the relationship between ESM and Workplace Isolation.  Experts and/or administrators should pay consideration to the impact of using ESM on agility and team performance of the workers. In addition, when implementing ESM to increase team performance they should concentrate on the extent of team diversity. By presenting the relationship between use of ESM, isolation in the workplace, workplace integration, agility of workers and performance of teams; it enriches the ESM use works by exploring the moderating functions of workplace integration while describing the beneficial consequences of workplace integration.